2014
DOI: 10.1037/hea0000031
|View full text |Cite
|
Sign up to set email alerts
|

Social oppression, psychological vulnerability, and unprotected intercourse among young Black men who have sex with men.

Abstract: Social oppression contributes to YBMSM's psychological vulnerabilities, participation in difficult sexual situations, and their UAI. Interventions to reduce sexual risk in YBMSM should address socioeconomic disadvantage, homophobia, and racism, as well as the psychological challenges that social oppression creates for them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 68 publications
1
35
2
Order By: Relevance
“…Participants were recruited using a modified venue-based time-location sampling protocol modeled after that used for the National HIV Behavioral Surveillance Survey [37], and adapted based on pilot work that established its feasibility in recruiting young Black MSM in these specific communities [38, 39]. Venues included bars, dance clubs, retail establishments, restaurants and cafés, adult bookstores, bath-houses, high-traffic street locations, parks, and other locations of social or religious organizations.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were recruited using a modified venue-based time-location sampling protocol modeled after that used for the National HIV Behavioral Surveillance Survey [37], and adapted based on pilot work that established its feasibility in recruiting young Black MSM in these specific communities [38, 39]. Venues included bars, dance clubs, retail establishments, restaurants and cafés, adult bookstores, bath-houses, high-traffic street locations, parks, and other locations of social or religious organizations.…”
Section: Methodsmentioning
confidence: 99%
“…The experience of social marginalization, along with how other demographic, socioeconomic, and sociocultural factors relate to increased HIV rates in the MSM population, is poorly understood (Huebner et al, 2013;Mizuno et al, 2012). Through a review of the literature, we have identified three factors that should be addressed to reduce HIV transmission in this population: masculinity, racial norms, and homophobia.…”
Section: Evidence-based Interventionsmentioning
confidence: 95%
“…Homophobia is linked to unprotected receptive anal intercourse as a result of MSM experiencing depression, decreased social support, and internalized homophobia; it is directly associated with having sex in difficult situations (Huebner et al, 2013). The mechanisms that link homophobia to these outcomes have yet to be elucidated; however, it has been suggested that these situations are key to understanding how homophobia and other forms of social discrimination can result in risky sexual behavior (Huebner et al, 2013).…”
Section: How Is Homophobia Linked To Hiv Transmission?mentioning
confidence: 98%
See 2 more Smart Citations